Voluminous, repetitive, and intractable: Samuelson on early development economics - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2020)
In the late 1970s Paul Samuelson drafted the outline of a paper, never published, with a critical assessment of the theoretical innovations of postwar development economics. He found the subject essentially intractable. The present paper discusses how that assessment fits in Samuelson's published writings on economic development, throughout several editions of his textbook Economics and in some papers he wrote after that assessment. Increasing returns posed a main analytical hurdle, together with the elusive attempt to provide "laws of motion" of economic development. Samuelson's notion of "tractability" may be traced back to Peter Medawar's well-known definition of science as the "art of the soluble."
Keywords: B20; B40; O10; 330; Samuelson; development economics; tractability; Medawar; increasing returns